Carbon-doped titania flakes with an octahedral bipyramid skeleton structure for the visible-light photocatalytic mineralization of ciprofloxacin. Issue 119 (17th November 2015) - Shi, Jian-Wen; Wang, Zhenyu; He, Chi; Li, Guodong; Niu, Chunming
Abstract : A novel and unique structure, an octahedral bipyramid skeleton, assembled by three pieces of carbon self-doped TiO2 flakes with exposed 001 facets was successfully prepared for the first time. Abstract : Pharmaceutical and Personal Care Products (PPCPs) are emerging contaminants, which can affect water quality and potentially impact drinking water supplies, ecosystems and human health. A novel and unique structure, an octahedral bipyramid skeleton, assembled by three pieces of carbon self-doped TiO2 flakes with exposed 001 facets was explored for the first time to mineralize ciprofloxacin, one of PPCPs. The results demonstrated that the obtained C-doped TiO2 flakes presented higher visible-light photocatalytic activity in comparison with the reported C-doped TiO2 sheets with exposed 001 facets, which can be ascribed to the narrower band gap, the higher percentage of the exposed 001 facts, the larger specific surface area, and the unique octahedral bipyramid skeleton structure.